Mengungkap Fenomena Turnover pada Generasi Y di Indonesia: Sebuah Kajian Literatur - Gebi Angelina Zahra; Kukuh Setyo Pambudi (Flourishing Journal, 2022)
Turnover is a phenomenon that often occurs among generation Y employees in Indonesia. This study aims to reveal the causes and impacts of turnover among generation Y in Indonesia by using the literature review method. The authors searched and evaluated scientific sources related to the research theme from various media such as journals, books, internet, etc. The results showed that turnover among generation Y in Indonesia was influenced by several factors, such as: low employee engagement, work life balance imbalance, lack of career opportunities, and high job demands. Turnover among generation Y in Indonesia also caused some negative impacts, such as: decreased productivity and work quality, increased recruitment and training costs, and loss of organizational knowledge and skills. This study provides suggestions and recommendations for managers and HR practitioners to reduce turnover among generation Y in Indonesia by increasing employee engagement, creating a harmonious work life balance, providing fair and transparent career opportunities, and adjusting job demands to the abilities and interests of employees. Abstrak Turnover merupakan fenomena yang sering terjadi pada karyawan generasi Y di Indonesia. Penelitian ini bertujuan untuk mengungkap penyebab dan dampak turnover pada generasi Y di Indonesia dengan menggunakan metode literature riview. Penulis melakukan pencarian dan evaluasi sumber-sumber ilmiah yang berkaitan dengan tema penelitian dari berbagai media seperti jurnal, buku, internet, dll. Hasil penelitian menunjukkan bahwa turnover pada generasi Y di Indonesia dipengaruhi oleh beberapa faktor, antara lain: rendahnya employee engagement, ketidakseimbangan work life balance, kurangnya kesempatan karier, dan tingginya tuntutan pekerjaan. Turnover pada generasi Y di Indonesia juga menimbulkan beberapa dampak negatif, seperti: menurunnya produktivitas dan kualitas kerja, meningkatnya biaya rekrutmen dan pelatihan, serta hilangnya pengetahuan dan keterampilan organisasi. Penelitian ini memberikan saran dan rekomendasi bagi para manajer dan praktisi SDM untuk mengurangi turnover pada generasi Y di Indonesia dengan cara: meningkatkan employee engagement, menciptakan work life balance yang harmonis, memberikan kesempatan karier yang adil dan transparan, serta menyesuaikan tuntutan pekerjaan dengan kemampuan dan minat karyawan.